2021
DOI: 10.5489/cuaj.7229
|View full text |Cite
|
Sign up to set email alerts
|

The second victim requires more than Medice Cura Te Ipsum

Abstract: Burnout has attained epidemic proportions in all reaches of society. Only recently, has its impact in healthcare become a burning platform. Second victim syndrome, a consequence of an unforeseen adverse event, often precipitated by an error, can lead to a post-traumatic stress-like reaction, that is unique to healthcare workers. Often, the second victim suffers in silence, forced to rely on resilience. Peer support has been demonstrated to be beneficial in assisting healthcare workers in recovering from both b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This study suggests that surgical trainees in Ireland do not feel ready to manage the emotional impact of AEs or complications and that their training could prepare them more effectively. This has been mirrored in international surveys with recommendations that healthcare organisations and training bodies take steps to introduce support systems and training for healthcare workers [6,11,12,29,32].…”
Section: Preparedness For Eventmentioning
confidence: 98%
See 1 more Smart Citation
“…This study suggests that surgical trainees in Ireland do not feel ready to manage the emotional impact of AEs or complications and that their training could prepare them more effectively. This has been mirrored in international surveys with recommendations that healthcare organisations and training bodies take steps to introduce support systems and training for healthcare workers [6,11,12,29,32].…”
Section: Preparedness For Eventmentioning
confidence: 98%
“…Despite this, our respondents still have symptoms suggestive of emotional distress and felt unprepared to manage it. Potential solutions include confidential peer support programmes as described above, emotional first aid, prompt debriefing and the opportunity for a break from professional activities [6,11,12,21,28,29,32]. There will also be a requirement for a larger cultural shift to a 'no blame' open culture, and normalisation of engagement with support services [15,28].…”
Section: Preparedness For Eventmentioning
confidence: 99%
“…As Dr. Koyle puts it, "Our calling in healthcare is to help others, and that also means one another, not just patients… don't let your colleagues suffer in silence and alone." 3…”
mentioning
confidence: 99%
“…Therefore, healthcare organisations should consider lessons learnt from these services with excellent institutionalized care for their workers. 8 Scott et al identified a predictable pattern of recovery for second victims (Table 1). 9 The first three stages can happen concurrently, or in quick succession.…”
mentioning
confidence: 99%